Utilization of aluminum plant's waste for production of insulation bricks - Mandal A.K.; Verma H.R.; Sinha O.P. (My University, 2025)
The fly ash (FA) and red mud (RM) are the primary solid waste produced in the aluminum plant. Present work investigates the possible utilization of these wastes for preparation of insulation bricks by blending different proportion of their mixture with sawdust. Study of the effect of varying FA:RM ratio, firing temperature (Tf) and sawdust blending on the physical properties of bricks has been carried out. Bricks having 60:40 ratio of FA:RM were found to possess maximum strength independent of Tf. It showed that higher firing temperature increases the strength of bricks. The blending of sawdust improves the porosity and the thermal insulation properties of the bricks. Bricks fired at 1100 °C and made by blending of minimum 7.5% saw dust, with 40% red mud in fly ash fulfills the criterion of ‘Type- A' insulation brick as per IS:2042 standards. These bricks are suitable for insulation in the ambiance having low to medium temperature (up to 600 °C) applications. © 2017 Elsevier Ltd